Innovacionnye technologii podgotovki professional'nych sportivno-igrovyck komand - Chernov, S. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
In the last years many kinds of sports-game activity at the level of maximum achievements have taken practically completed form of professional sports. In basketball it is basically based on the realization of the highly effective sports activity in intense and spectacular-attractive conditions. Simultaneously the purposes to perform not only effective, but also striking game actions are directly formed at players. Thus, as well as in sports of the maximum achievements, the final result in the form of sports success is the main criterion of effective activity.